2021
DOI: 10.25259/sni_593_2021
|View full text |Cite
|
Sign up to set email alerts
|

Surgical correction of pediatric spinal deformities with coexisting intraspinal pathology: A case report and literature review

Abstract: Background: Surgical correction of spinal deformities with coexisting intraspinal pathology (SDCIP) requires special consideration to minimize risks of further injury to an already abnormal spinal cord. However, there is a paucity of literature on this topic. Here, the authors present a pediatric patient with a residual pilocytic astrocytoma and syringomyelia who underwent surgical correction of progressive postlaminectomy kyphoscoliosis. Techniques employed are compared to those in the literature to compile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…There exists a paucity of surgical guidelines for correcting spinal deformity associated with pediatric spinal tumors – before or after tumor resection. A recent review by Li et al [13] of the MEDLINE database between 1969 and 2019 found only four articles that described approaches and surgical techniques for correction of post-laminectomy deformity after pediatric tumor resection. When their search was broadened to include all intraspinal pathology (including tethered cord, syringomyelia, and diastematomyelia), additional nine articles were found.…”
Section: Correcting Deformitymentioning
confidence: 99%
See 1 more Smart Citation
“…There exists a paucity of surgical guidelines for correcting spinal deformity associated with pediatric spinal tumors – before or after tumor resection. A recent review by Li et al [13] of the MEDLINE database between 1969 and 2019 found only four articles that described approaches and surgical techniques for correction of post-laminectomy deformity after pediatric tumor resection. When their search was broadened to include all intraspinal pathology (including tethered cord, syringomyelia, and diastematomyelia), additional nine articles were found.…”
Section: Correcting Deformitymentioning
confidence: 99%
“…Decompression of neural elements and resection of oncologic pathology, where possible, should precede manipulation of the spine and correction of deformity. Li et al [13] further recommend avoiding distractive maneuvers in favor of compressive maneuvers to avoid overlengthening of the canal and stretching of the spinal cord in the setting of intraspinal masses.…”
Section: Correcting Deformitymentioning
confidence: 99%
“… 3 , 4 There is, however, no current guideline for surgical correction. 5 In cases of extreme kyphoscoliosis (>60° in the sagittal plane), double pedicle subtraction osteotomy (PSO) conducted at the lower thoracic and L2–3 vertebrae has been found to be effective in correcting spine misalignment. 6 , 7 Unfortunately, PSO requires a longer operative time than lower-grade osteotomies, carrying greater associated blood loss and risk of neurological injury.…”
mentioning
confidence: 99%